A longitudinal study of thyroid markers during pregnancy and the risk of gestational diabetes mellitus and post‐partum glucose metabolism. Issue 4 (22nd February 2021) - Tang, Lei; Li, Ping; Zhou, Hua; Li, Ling
Abstract: Aims: To determine the relationship between thyroid markers during pregnancy and gestational diabetes mellitus (GDM) or post‐partum glucose metabolism. Materials and Methods: Based on pregnancy 75‐g oral glucose tolerance test (OGTT) results, 1467 subjects were grouped into normal glucose tolerance (NGTp; n = 768) and GDM ( n = 699) groups. Furthermore, based on post‐partum 75‐g OGTT results, 286 GDM subjects, screened for glucose metabolism after delivery, were grouped into NGTd ( n = 241) and abnormal glucose tolerance (AGT; n = 45) groups. Results: Maternal age, family history of diabetes, acanthosis nigricans, previous adverse pregnancy outcomes and caesarean section incidence, and thyroid positive antibody rates were higher in the GDM group than in the NGTp group. In the first trimester, free triiodothyronine (FT3), thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb) levels were higher in the GDM group than in the NGTp group. In the second trimester, free thyroxine (FT4) levels were lower and TPOAb and TgAb levels were higher in the GDM group than in the NGTp group. After adjusting for confounding factors, FT3, TPOAb and TgAb (first trimester), and FT4, TPOAb and TgAb (second trimester) were risk factors for GDM. TPOAb and TgAb levels were higher in the AGT group than in the NGTd group and were potential predictors of abnormal post‐partum glucose tolerance. Conclusions: GDM risk significantly increased with increased FT3 (first trimester), TPOAb and TgAb (first and second trimesters) or with decreased FT4 (second trimester). Presence of thyroid antibodies predicted post‐partum glucose abnormalities in subjects with GDM.